Collaborative Reflection to Enhance Teachers’ Teaching Ability Utilized Inquiry Model - Tani, Richa Widya; Putra, M. Jaya Adi; Marhadi, Hendri (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
This research aims to explore the prospective teachers activities to enhance teachers’ teaching skills utilized inquiry by perform reflective collaborative activities between teachers, coaches and prospective teachers. Activities reflection helps prospective teachers make improvements in the implementation of tasks so that for further learning meetings prospective teachers can improve teaching skills. Improved teaching ability to give impact on teacher activities and students who experience improvement at each meeting so that it has an influence on student learning outcomes. In understanding the concept of students' average heat energy increased from the average base score of 64.91 to 76.22. In understanding the concept of average student sound energy from the basic score to 81.72. The increase of learning result can be seen from the average of N-Gain on the understanding of the concept of heat energy of 0.32 medium categories and on the understanding of energy concept of 0.47 medium categories. This study concluded that the application of inquiry learning model can improve science learning outcomes based on reflection by prospective teachers.